2017
DOI: 10.1002/ajpa.23176
|View full text |Cite
|
Sign up to set email alerts
|

Domestication and human demographic history in South America

Abstract: In this work we uncovered a well-supported pattern of the demographic change in the populations from South-Central Andes and Patagonia, obtained on the basis of different data and quantitative approaches, which suggests that the incorporation of domestic resources was paramount for the demographic expansion of these populations during the Holocene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
0
23
0
1
Order By: Relevance
“…Colonising groups successfully adapted to a broad range of environments during the Terminal Pleistocene and early Holocene, from the Amazonian rainforest and Patagonian grasslands to the high Andes 1–4 . The genetic and demographic structure of early populations have been the focus of substantial recent research 5,6 . In parallel, a growing body of archaeological evidence from several regions has suggested that climatic transitions acted as a driver of significant regional depopulation during the mid-Holocene.…”
Section: Introductionmentioning
confidence: 99%
“…Colonising groups successfully adapted to a broad range of environments during the Terminal Pleistocene and early Holocene, from the Amazonian rainforest and Patagonian grasslands to the high Andes 1–4 . The genetic and demographic structure of early populations have been the focus of substantial recent research 5,6 . In parallel, a growing body of archaeological evidence from several regions has suggested that climatic transitions acted as a driver of significant regional depopulation during the mid-Holocene.…”
Section: Introductionmentioning
confidence: 99%
“…With reference to the systems driving rainfall variability across South America (Supplementary Information), these regions respectively approximate areas principally influenced by moisture transportation from the Atlantic, areas influenced by the Atlantic and potentially Pacific sources, and predominantly South Pacific/South Atlantic-influenced zones 13,[23][24][25] . The Southern Cone, as defined here, also acts as a geographical proxy for the southern limits of tropical domesticates prior to the beginning of the late Holocene 6,26 . We take consistent patterns in the radiocarbon data to reflect robust and independent trends in human population across regions rather than specific archaeological cultures.…”
mentioning
confidence: 99%
“…Recent studies have marshalled population genetics, geoarchaeology, and importantly, climate archives to contextualise the wealth of data on pre-Columbian demographic processes (Keefer et al 2003;Dillehay and Kolata et al 2004;Fehren-Schmitz et al 2014;Perez et al 2017). Figure 5a-c presents three palaeoclimatic archives for the Holocene that are of especial importance to contextualising millennial-scale demographic patterns illustrated by the model and permutation testing.…”
Section: Discussionmentioning
confidence: 99%